A framework for generating prioritised test scenarios using firefly optimisation technique. (2017) - Panthi, Vikas; Mohapatra, Durga Prasad
The intention of this research is to generate test scenarios for concurrent and composite states in state machines using firefly optimisation algorithm. We have used state-based coverage criterion such as state coverage, transition coverage, transition pair coverage, etc. to evaluate the efficiency of our proposed algorithm. The proposed approach is useful for feasible test scenario generation. Generating exhaustive test scenarios for all concurrent interdependent sequences is exponential in size. As a result, in this paper, we find the important test scenarios in the presence of concurrency in composite models.